Assessment of Investment Projects Based on Economic Flow and Not in Cash Flows - Kukaj, Halil; Morina, Fisnik (European Journal of Sustainable Development, 2019)
In terms of global competitiveness, taking the investments decisions has a great impact to remain in the market. For this, when evaluating the investing projects it is necessary to apply the methods of profitability and liquidity. However, the question arises, if the profitability evaluation of investing project should be made according to the cash flow or the data from the economical flow statement. The aim of this paper is to give arguments why the economical flow statement should be applied instead of cash flow statement for the evaluation of profitability of investing projects. The paper is based on a hypothetical example whereas arguments are derived while applying the indicators: the Net present value and internal norm of profitability. Keywords: Evaluation of investing project, economical flow, net present value, internal norm of profitability